What is new in peripartum hysterectomy? A seventeen year experience in a tertiary hospital - Gonca Yetkin Yildirim; Nadiye Koroglu; Aysu Akca; Merve Talmac; Selin Dikmen; Gokhan Yıldırım; Ibrahim Polat; Ismail Ozdemir (Elsevier, 2021)
Objective: To identify changing trends in peripartum hysterectomy (PH), both elective.cesarean hysterectomy and emergency cesarean hysterectomy, at a single training and research hospital over the last 17 years in Istanbul, Turkey. Materials and methods: A retrospective cohort study was performed between January 2001 and September 2017. The records of all patients who had PH at Kanuni Sultan Süleyman Training and Research Hospital were analyzed. Results: There were 243 cases of PH during the study period. A total of 266,386 births occurred, of which 60.1% were vaginal deliveries and 39.8% were cesarean sections. The incidence of PH increased from 0.67 per 1000 deliveries to 1.14 per 1000 deliveries during 2001-2008 and 2009-2017, respectively, with an overall incidence of 0.91 per 1000 deliveries during the 17 years. The main indication for PH changed significantly during this time from uterine atony (57.1%) to placenta accreta spectrum (85%). About 37% of women who underwent PH had at least one previous cesarean delivery during 2001-2008, whereas that percentage increased to 95.4% during 2009-2017. Conclusion: Placenta accreta spectrum was the leading cause of PH and was associated with significant maternal morbidity and mortality.